Potret Penguasaan Komputer dan Aplikasi Perkantoran Mahasiswa Fakultas Dakwah dan Ilmu Komunikasi UIN Imam Bonjol Padang - Benny Benny (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2020)
The advancement of technological inventions has made a lot of works become computerized. Various jobs have changed into new models that require workers must have computer skills or basic of computer operations. Therefore, colleges as the highest education are responsible to ensure the computer skills of its alumni to be ready in competing with others in the workplace. Through a quantitative approach, this study tried to see the level of college students' computer mastery of Da'wah and Communication faculty at UIN Imam Bonjo Padangl. By involving 90 samples of college students in the faculty, it was found that the level of students' computer mastery was on medium category. Meanwhile, the level of students' office application mastery had various findings. For the level of students' mastery on Microsoft Word and Power point, it was on medium category. But, for students' office application mastery on Microsoft Excel was on low category.